Advances in Key Drug Target Identification and New Drug Development for Tuberculosis. - Mi, Jie; Gong, Wenping; Wu, Xueqiong (BioMed Research International, 2022)
Tuberculosis (TB) is a severe infectious disease worldwide. The increasing emergence of drug-resistant Mycobacterium tuberculosis (Mtb) has markedly hampered TB control. Therefore, there is an urgent need to develop new anti-TB drugs to treat drug-resistant TB and shorten the standard therapy. The discovery of targets of drug action will lay a theoretical foundation for new drug development. With the development of molecular biology and the success of Mtb genome sequencing, great progress has been made in the discovery of new targets and their relevant inhibitors. In this review, we summarized 45 important drug targets and 15 new drugs that are currently being tested in clinical stages and several prospective molecules that are still at the level of preclinical studies. A comprehensive understanding of the drug targets of Mtb can provide extensive insights into the development of safer and more efficient drugs and may contribute new ideas for TB control and treatment.